Development of Otam – Molibagu TL 150 kV Transmission Design which is Environmentally Friendly - Musliani, Musliani; Desi, Natsar; Anugrah, Anugrah (Universitas Ibn Khaldun Bogor, 2023)
Population growth is increasing every yearrequires more and more energy requirements, especially on the electrical energy side, namely the increasing demand for electric power.Although the technology for the construction of power plants and their transmission systems has been pursued with more sophisticated, effective, efficient and safe technologies, the obstacles still exist, one of which is the increasing difficulty of placing high-voltage transmission lines that are free from settlements and the influence of electric field radiation. and magnetic fields on human health has become an environmental problem for PT. PLN (Persero). This study aims to determine how much safe voltage is for people who pass through the High Voltage Air Lines and develop construction designs. The data analysis technique used by the author is descriptive qualitative analysis. The results of monitoring the magnetic field on the 150kV SUTT transmission is 0.5 mT while the electric field strength is 70 V/m. in Bolaang Mangandow Selatan is safe for human health based on standards.